Defect-rich CoFe-alloy with engineered carbon support for high-performance rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Barik, Sidharth; Torris, Arun; Maria, Anit; Kumar, Yogesh; Kurungot, Sreekumar (Small, 2025)
Defect-rich CoFe-alloy with engineered carbon support is synthesized as a bifunctional cathode, coupled with a modified electrode fabrication technique, for rechargeable zinc-air batteries (RZABs). The CoFe(2:1)/N-rGCNT-catalyst is synthesized by annealing graphene oxide (GO), cobalt and iron acetate, and melamine, leading to the in situ formation of CoFe alloy-encapsulated CNTs. This resulted in a unique layer-separated Fe-rich skin@CoFe alloy decorated nitrogen-doped graphene (NGr) with CoFe-encapsulated CNTs. The interplay of line defects, enhanced conductivity, and electronic modulation underpins electrocatalyst's performance. Electrochemical analysis revealed an onset potential of 955 mV vs RHE, a half-wave potential of 835 mV vs RHE for oxygen reduction reaction (ORR) and an overpotential of 340 mV for oxygen evolution reaction (OER), yielding a Delta E of 0.73 V, comparable to the reported catalysts. The 3D X-ray microtomography simulations suggest improved air permeability of CoFe(2:1)/N-rGCNT facilitates easier gas diffusion, contributing in better device performance. The RZAB with CoFe(2:1)/N-rGCNT-cathode exhibited a peak power density of 171.3 mW cm(-)2, surpassing 140.8 mW cm(-)2 obtained from a cell based on Pt/C-cathode. The Co/N-rGCNT-based battery achieved a stable discharge profile at 10 mA cm(-)2 with a specific capacity of 650 mAh g(-)(1)Zn, and in rechargeable mode, achieved 140 h of high-rate charge-discharge cycling capability.
Keywords: 3D tomography; N-doping; alloy encapsulated structure; device demonstration; grain boundaries; oxygen reduction and evolution reactions; rechargeable zinc-air battery